2019
DOI: 10.3390/w11061228
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Splash Erosion Devices for Rainfall Simulation Experiments: A Laboratory Study

Abstract: For the study of soil erosion it is important to set up the experiments well. In the experimental design one of the key factors is the choice of the measurement device. This is especially important when one part of the erosion process needs to be isolated, such as for splash erosion. Therefore, the main aim of this research is to list the general characteristics of the commonly used splash erosion devices and to discuss the performance, to be able to relate them, and make suggestions regarding their use. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 57 publications
(83 reference statements)
1
28
0
Order By: Relevance
“…The overall relationship between the mass of the eroded particles and the rainfall kinetic energy has a linear trend ( Figure 5). The coefficient of determination is 0.7 which is higher than or in a similar range as presented in comparable studies (e.g., [6,15,41]). Table 1 summarizes selected splash erosion experiments from the literature to show how the experiments vary in setup.…”
Section: Resultssupporting
confidence: 45%
See 3 more Smart Citations
“…The overall relationship between the mass of the eroded particles and the rainfall kinetic energy has a linear trend ( Figure 5). The coefficient of determination is 0.7 which is higher than or in a similar range as presented in comparable studies (e.g., [6,15,41]). Table 1 summarizes selected splash erosion experiments from the literature to show how the experiments vary in setup.…”
Section: Resultssupporting
confidence: 45%
“…They show similar, most often linear, relationships between the amount of detached soil particles and various rainfall characteristics. The slope of the linear trendline differs in each study because of differing experimental setups (rainfall duration, sample preparation) and soil properties [6,15,42]. Bisal [17] and Mazurak and Mosher [18] already experimentally showed that the splashed amount is linearly dependent on drop size and velocity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To understand soil erosion processes, each pedological, climate, geomorphological and hydrological parameter must be assessed. In Fernández-Raga et al [10], the authors highlighted the need to choose the most correct measurement device during the experimental design; for example, in the case of splash erosion. They evaluated the hydrological response under different intensities of simulated rainfall of different devices under the same conditions.…”
Section: Summary Of This Special Issuementioning
confidence: 99%